Lipid Oxidation in Oil‐in‐Water Emulsions: Involvement of the Interfacial Layer. Issue 5 (September 2014) - Berton‐Carabin, Claire C.; Ropers, Marie‐Hélène; Genot, Claude
Abstract More polyunsaturated fats in processed foods and fewer additives are a huge demand of public health agencies and consumers. Consequently, although foods have an enhanced tendency to oxidize, the usage of antioxidants, especially synthetic antioxidants, is restrained. An alternate solution is to better control the localization of reactants inside the food matrix to limit oxidation. This review establishes the state‐of‐the‐art on lipid oxidation in oil‐in‐water (O/W) emulsions, with an emphasis on the role of the interfacial region, a critical area in the system in that respect. We first provide a summary on the essential basic knowledge regarding (i) the structure of O/W emulsions and interfaces and (ii) the general mechanisms of lipid oxidation. Then, we discuss the factors involved in the development of lipid oxidation in O/W emulsions with a special focus on the role played by the interfacial region. The multiple effects that can be attributed to emulsifiers according to their chemical structure and their location, and the interrelationships between the parameters that define the physicochemistry and structure of emulsions are highlighted. This work sheds new light on the interpretation of reported results that are sometimes ambiguous or contradictory.